Prevalence and Predictors of High-Grade Anal Dysplasia in People With HIV in One Southeastern Ryan White HIV/AIDS Program Clinic. (21st October 2022) - Geba, Maria; Cardenas, Benjamin; Williams, Brooke; Hoang, Sook; Newberry, Yvonne; Dillingham, Rebecca; Thomas, Tania A
Abstract: Background: Prevalence of anal cancer is increasing among people with HIV (PWH). Screening for anal cancer involves evaluating cytology and biopsy with high-resolution anoscopy (HRA) if indicated. In this study, we sought to identify the prevalence of abnormal anal cytology and biopsy-proven high-grade dysplasia, defined as anal intraepithelial neoplasia 2 and 3 (AIN2+). Methods: Demographic and clinical data were collected from participants age ≥30 years with ≥1 anal Pap smear performed during the study period (12/18/2017–05/29/2021). A subgroup analysis was performed on those with ≥1 HRA. Logistic regression estimated adjusted odds ratios (aORs) for variables of interest such as age, race, gender, presence of HPV strains, and sexual practices. Results: Of 317 participants, 48% (n = 152) had abnormal cytology (93% low-grade squamous intraepithelial lesion [SIL] or atypical cells of undetermined significance [ASCUS] and 7% high-grade SIL). Most with abnormal cytology proceeded to HRA (n = 136/152). Of those with HRA, 62% (n = 84/136) had AIN2+. History of anoreceptive intercourse (aOR 4.62; 95% CI 1.08–23.09; P = .047), HPV 16 (aOR 4.13; 95% CI 1.63–11.30; P = .004), and "other" high-risk HPV strains (aOR 5.66; 95% CI 2.31–14.78; P < .001) were significantly associated with AIN2+. Conclusions: Nearly half of those screened had abnormal cytology, highlighting the high prevalence of anal dysplasia in PWH. Though only 7% had high-grade SIL on cytology, 62% of those biopsied had AIN2+, suggesting that cytology underestimates the severity of dysplasia on biopsy. HPV 16 and "other" high-risk strains were associated with AIN2 + and could be considered for risk-stratifying patients in the screening algorithm.